Treatment of patients with comorbid depression and diabetes with metformin and milnacipran - Peter Hofmann (Dove Medical Press, 2010)
Peter HofmannUniversity Clinic of Psychiatry, Graz Medical University, Graz, AustriaAbstract: Depression is twice as frequent in patients with diabetes as in the general population, and has a negative impact on self-care, adherence to treatment, and the general prognosis of diabetes. This underscores the importance of screening all diabetic patients for depression and, if necessary, treating it with an effective antidepressant drug in parallel with standard diabetes treatment. In a recent study, a simple two-question screening tool was used to screen diabetic patients for comorbid depression. The effects of the serotonin and norepinephrine reuptake inhibitor antidepressant, milnacipran, on metabolic parameters and depressive symptoms in 64 diabetic patients with comorbid depression detected by this screen were studied. Patients received milnacipran for 6 months, in addition to standard diabetes treatment with metformin. At the end of the study, 72% of patients had responded to antidepressant treatment (≥50% reduction of baseline Beck Depression Score). The proportion of patients with <8% glycosylated hemoglobin HbA1c (a common indication in diabetes of the need for intensive therapeutic intervention) had decreased significantly from 46.6% at baseline to 6.9%. HbA1c, fasting blood glucose, body mass index, total and low-density lipoprotein cholesterol, and serum triglyceride levels were all significantly decreased in patients with an antidepressant response, but not in patients whose depressive symptoms had not responded to milnacipran.Keywords: depression, diabetes, milnacipran, serotonin, norepinephrine, reuptake inhibitors